Avaliação de soros hiperimunes anti-Brucella para detecção de Brucella spp. por imunoistoquímica - Brunno Gardiman Sossai (2021)
Brucellosis is an important zoonotic infectious disease with worldwide distribution. It has a chronic course that mainly causes reproductive changes in domestic and wild animals. Identification of infected animals occurs through clinical evaluation, associated with direct or indirect diagnostic tests. The present study aimed to evaluate the efficacy of four different rabbit hyperimmune anti-Brucella sera for detection of Brucella spp. antigens in paraffinized tissues of animals experimentally or naturally infected with B. abortus, B. canis, or B. ovis. The hyperimmune sera were produced by immunizing four rabbits, with a Brucella spp. inactivated by gamma radiation, or with a recombinant BP26 protein. ELISA test was used to determine the serum conversion of the rabbits to the immunization and cross-reactivity of the hyperimmune sera to the antigens. Immunohistochemistry was performed with three dilutions (1/100, 1/500, and 1/1000) of the hyperimmune sera to determine the ideal dilution for use and cross-reactivity. It was observed that anti-B. abortus and anti-B. ovis antibodies detected a greater number of cases of animals affected by brucellosis, anti-B. canis antibody showed lower detection and anti-BP26 serum did not identify any infected animal. Immunization of rabbits with radiation inactivated Brucella spp. produced anti-Brucella hyperimmune sera effective in identifying the Brucella antigens in the lesion, but the anti-BP26 hyperimmune serum was not able to identify those antigens.